An Empirical Study on the Impact of Sustainable Manufacturing Practices and Innovation Performance on Environmental Sustainability - Hami, Norsiah; Muhammad, Mohd Razali; Ebrahim, Zuhriah (UTM Press, 2015)
This study analyzes the causal relationship between sustainable manufacturing practice (SMP) and environmental sustainability as well as determines the mediating effect of innovation performance (IP) on the relationship between SMP and environmental sustainability. Adaptation from the changing business environment, manufacturing firms are facing great challenge on producing more products with less resource consumption, pollution emitted and waste generated. Using structural equation modeling, the survey data collected from 150 Malaysian manufacturing firms has been analyzed in this study. The empirical results show that both types of SMP have a positive and significant impact on environmental sustainability with external SMP is greater than internal SMP. However, there is no significant evidence to prove IP as a mediator for SMP-environmental sustainability linkage. The findings of this paper have important implication in both theoretical and practical perspectives. While provide better understanding of the phenomena by simultaneously analyzing a series of dependence relationships among SMP, IP and environmental sustainability, these results could help managers to understand the types of practices that would improve their environmental performance